Effect of Dyslipidemia Therapy on Creatinine Kinase Activity Level in Patients with Heart Disease - Sulistian, Waode Dila; Fuadi, Muhamad Ro’biul; Edijanto, Soebagijo Poegoeh; Yusuf, Mochammad (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Cardiovascular disease remains a significant health problem in the Asia Pacific region. Several studies have found that dyslipidemia is a cause of morbidity and mortality and requires high medical costs. Dyslipidemia is a risk factor for atherosclerosis. The most widely used therapy for dyslipidemia is statins. Statins often cause muscle disorders such as myalgia, myopathy, and rhabdomyolysis, which can cause death. A prospective cohort study design was carried out at Airlangga University Hospital, Surabaya, from April to November 2019. A total of 26 sample pairs containing 13 samples were treated with Atorvastatin, and 13 samples were treated with Simvastatin. The subjects were examined for the creatinine kinase activity level using enzymatic methods. The mean creatinine kinase levels in the atorvastatin group before and after treatment was 105.71 IU/L and 100.03 IU/L, respectively, because the subjects were diagnosed with acute coronary syndromes and blood was collected during acute conditions. Median creatinine kinase levels in the Simvastatin group were 85.5 IU/L before therapy and 118.1 IU/L after therapy, indicating significant differences in creatinine kinase levels before and after treatment. Simvastatin is very susceptible to certain drug interactions that can increase the concentration of statins in the serum. There were differences in levels of creatinine kinase activity before and after Simvastatin therapy but not Atorvastatin.